Numerical Simulation Study on Fish Habitats in the Downstream Section of Yangqu Hydropower Station - Qiaoling Zhang; Youjie Ou; Weiying Wang; Guoyong Zhang; Zijun Liu; Shanshan Li; Guodong Li (Ecology and Evolution)
ABSTRACT To promote the coordinated and sustainable development of hydropower exploitation and ecological environment in the upper reaches of the Yellow River, a fine simulation of the downstream riverway of Yangqu Hydropower Station was carried out to analyze the impact of the changes in water depth and flow velocity on fish habitats after the impoundment of Yangqu Hydropower Station. In this paper, Gymnocypris eckloni was selected as the target fish species. The fish habitat model was constructed using MIKE21. The habitat quality of the target fish species was graded by the fuzzy logic method with suitable flow velocity and water depth as conditions. The Weighted Usable Area (WUA)—flow response relationship of fish habitats under different qualities was studied, and the ecological flow required by the target fish species was obtained. The results indicated that the suitable ecological flow range, derived from the relationship between the weighted total area of habitats of different qualities and flow variations, ranged from 350 to 1100 m3/s. Furthermore, the suitable flow range determined through the proportion of WUA of habitats of different qualities was between 600 and 1150 m3/s. After a comprehensive analysis, the final suitable ecological flow range was determined to be 600 to 1150 m3/s. The proportion of high‐quality habitat WUA ranged from 0.26 to 0.50, As the traffic increased, it first increased and then decreased, and was most affected by changes in traffic, the proportion of medium‐quality habitat WUA fluctuated between 0.40 and 0.55, showing an overall upward trend. Meanwhile, the proportion of low‐quality habitat WUA increased from 0.11 to 0.21, indicating the smallest impact from flow variations. The research results could provide a certain reference for the ecological scheduling of hydropower stations in the upper reaches of the Yellow River.